A Different Kind of Medicinal Chemistry Toolbox - Huryn, Donna M. (ACS Med Chem Lett, 2020)
[Image: see text] To attract and retain women in medicinal chemistry, a toolbox of resources and opportunities is suggested. Scientific meetings, books, affinity groups, training courses, and networks all can provide support and strategies to help increase the percentage of women in the field.